A comparison between different selection indexes for milk and udder health traits on Holstein-Friesian cows in Egypt - Khattab, Adel Salah; Salem, Ahmed Hamed; Kassab, Manal; Tőzsér, János; Gabr, Ahmed Amr (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
A total of 937 normal lactation records of Holstein-Friesian cows, kept at Sakha Farm, belonging to Animal Research Institute Ministry of Agriculture, Dokki, Cairo, Egypt during the period from 2012 to 2017 were used to estimate phenotypic and genetic parameters for 305-day milk yield (MY10), lactation length (LL), fat percent (F%) and somatic cell count (SCC). Data were analyzed using Multiple Trait Derivate Free Restricted Maximum Likelihood (MTDFREML, Boldman et al. 1995). Means of MY10, LL, F% and SCC were 3558 kg, 301 d, 3.7% and 536x10-3, respectively. Month and year of parturition and parity had a significant effect on all most traits studied. Heritability estimates for MY10, LL, F% and SCC were 0.61±0.14, 0.16±0.07, 0.40±0.07 and 0.03±0.07, respectively. Eleven selection indexes were constructed. Index I1 incorporating the four traits was the best (RIH= 0.97). It is recommended for selection cows for milk traits and less somatic cell count.
Keywords: Holstein-Friesien cow; phenotypic and genetic parameters; selection indexes; Egypt